2010
DOI: 10.1182/blood.v116.21.2247.2247
|View full text |Cite
|
Sign up to set email alerts
|

Hypercholesterolemia and Its Association with Enhanced Stem Cell Mobilization and Harvest After High-Dose Cyclophosphamide + G-CSF

Abstract: 2247 Hematopoietic stem cells (HSC) reside in specific niches in the bone marrow and various signals regulate survival, self-renewal, proliferation, differentiation and trafficking. Egress of HSCs into the peripheral blood (PB) is enhanced by multiple agonists, although the exact mechanisms that regulate this critical process are largely unknown. After treatment with cyclophosphamide and G-CSF, long-term HSC in the bone marrow enter the cell cycle. Additionally, G-CSF induces a reduction of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…However, lack of detectability of sex influencing HSPC mobilization response in our study is likely due to small sample size. Oguro et al and others demonstrated that an estrogen receptor ligand is capable of HSPC mobilization through its effect on estrogen receptors, yet the role of estradiol in mobilization of HSPC remains to be investigated 32‐37 . Notably, cholesterol inhibitory drugs can augment HSPC mobilization independent of cholesterol metabolism such as by release of nitric oxide 38 .…”
Section: Discussionmentioning
confidence: 99%
“…However, lack of detectability of sex influencing HSPC mobilization response in our study is likely due to small sample size. Oguro et al and others demonstrated that an estrogen receptor ligand is capable of HSPC mobilization through its effect on estrogen receptors, yet the role of estradiol in mobilization of HSPC remains to be investigated 32‐37 . Notably, cholesterol inhibitory drugs can augment HSPC mobilization independent of cholesterol metabolism such as by release of nitric oxide 38 .…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Obesity may also foster the production of proinflammatory cytokines that stimulate tumor growth. 19,20 The adipose compartment contains hematopoietic stem cells, lymphocytes and other hematopoietic cells that may be pertinent to transplant biology and kinetics. 8,19,21,22 Understanding the factors resulting in decreased HPC mobilization is of major importance given the associated worse long-term transplant outcomes.…”
Section: Discussionmentioning
confidence: 99%